Serum Transcobalamin Concentration in Cats—Method Validation and Evaluation in Chronic Enteropathies and Other Conditions - Tim Kunath; Stefanie Kather; Franziska Dengler; Ebba Nexo; Helga Pfannkuche; Romy M. Heilmann (Veterinary Sciences)
Hypocobalaminemia is common in cats with chronic enteropathy (FCE). However, the disruptions in cobalamin metabolism are not fully understood and may vary across species. Cobalamin is distributed to target tissues via binding to transcobalamin (TC) in blood, which has not been evaluated in cats. Thus, an in-house sandwich-ELISA was established to evaluate serum total TC concentrations in cats with FCE. Surplus sera served to analytically validate the assay, and serum TC concentrations were compared among cats with FCE and other diseases (gastrointestinal neoplasia, cholangiohepatopathy, and other neoplastic or non-neoplastic conditions) and healthy controls. Observed-to-expected ratios for serial dilutions ranged from 72.4 to 145.6% and were 75.1–126.7% for spiking-and-recovery. Intra- and inter-assay variability was <17.7% and <17.2% and the preliminary reference interval for feline serum TC was <160–2795 aU/L (lower detection limit: 160 aU/L). Serum TC levels were significantly decreased (p = 0.0067) but not correlated with paired cobalamin concentrations in FCE. Hypertranscobalaminemia predominated with hypercobalaminemia, reaching the highest levels in advanced-stage chronic kidney disease (CKD) cases. TC variations in cobalamin deficiency states with FCE may be linked to inflammation or autoantibodies. This and possible links between serum TC variation in FCE, intracellular cobalamin availability, response to supplementation, and concurrent CKD require further exploration.